2000
DOI: 10.1103/physrevlett.84.3177
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt Appearance of the Domain Pattern and Fatigue of Thin Ferroelectric Films

Abstract: We study the domain structure in ferroelectric thin films with a 'passive' layer (material with damaged ferroelectric properties) at the interface between the film and electrodes within a continuous medium approximation. An abrupt transition from a monodomain to a polydomain state has been found with the increase of the 'passive' layer thickness d. The domain width changes very quickly at the transition (exponentially with d −2 ). We have estimated the dielectric response dP/dE (the slope of the hysteresis loo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
189
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(196 citation statements)
references
References 22 publications
(25 reference statements)
7
189
0
Order By: Relevance
“…We assume the film to be in the single-domain state, although the depolarizing field generally favors the formation of 180°domains. 33,34 This model enables us to determine the maximum effect of depolarizing field on the dielectric response of a ferroelectric film. Moreover, the application of an electric field stronger than the coercive field makes the film polarization state uniform on the macroscopic scale.…”
Section: Effect Of Depolarizing Field On Permittivity and Capacimentioning
confidence: 99%
“…We assume the film to be in the single-domain state, although the depolarizing field generally favors the formation of 180°domains. 33,34 This model enables us to determine the maximum effect of depolarizing field on the dielectric response of a ferroelectric film. Moreover, the application of an electric field stronger than the coercive field makes the film polarization state uniform on the macroscopic scale.…”
Section: Effect Of Depolarizing Field On Permittivity and Capacimentioning
confidence: 99%
“…Here C is the capacitance of the electroded FE film of area A, with L the separation between electrodes. Indeed, when the dead layer is thin, the domain width a becomes very large, it grows exponentially with 1/d 2 [1]. The response of this domain structure is very soft, and this should translate into very abrupt increase of the dielectric constant ǫ ef f of the capacitor.…”
mentioning
confidence: 99%
“…It has direct bearing on fatigue observed in FE capacitors since in many cases the deterioration of the switching behavior, like the loss of the coercive force and of the squareness of hysteresis loop, were attributed to the growth of a "passive layer" at the ferroelectricelectrode interface [2][3][4][5]. It is of principal importance that the presence of a dead layer, no matter how thin in comparison with thickness of the ferroelectric layer, triggers a formation of the domain structure in FE film [1]. We have shown that when the thickness of the dead layer d is not very small, the apparent (net) polarization P a of the ferroelectric with 180−degree domain walls follows an approximate relation dP a /dE ∝ ǫ g /d, which is in good correspondence with available experimental data (see e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…P=e 0 in SI units, " P is total polarization of the system) stabilizes 180°electrical domains [28][29][30] to compensate for the internal depolarization field induced by the variation of the order parameter near interfaces and due to imperfectly screening electrodes. One must keep in mind that the depolarization term in a FE is a function of sample shape and depends on the thickness for the case of a film that is infinite in the plane.…”
Section: Theory and Methodologymentioning
confidence: 99%